1999
DOI: 10.1121/1.424670
|View full text |Cite
|
Sign up to set email alerts
|

Speech intelligibility and localization in a multi-source environment

Abstract: Natural environments typically contain sound sources other than the source of interest that may interfere with the ability of listeners to extract information about the primary source. Studies of speech intelligibility and localization by normal-hearing listeners in the presence of competing speech are reported on in this work. One, two or three competing sentences [IEEE Trans. Audio Electroacoust. 17(3), 225-246 (1969)] were presented from various locations in the horizontal plane in several spatial configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
163
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 35 publications
4
163
1
Order By: Relevance
“…In general, informational masking is most likely to occur when the target and masker are similar to one another (e.g., when both a speech target and a speech masker are recorded from talkers of the same sex). A number of studies have demonstrated that both energetic and, in particular, informational masking can be reduced by spatially separating the target from the masker (e.g., Brungart & Simpson, 2002;Freyman, Balakrishnan, & Helfer, 2004;Freyman, et al, 1999Freyman, et al, , 2001Freyman, Helfer, & Balakrishnan, 2005;Hawley, Litovsky, & Colburn, 1999) although the mechanisms leading to spatial separation advantage seem to differ between the two types of masking. Specifically, even when the head shadow and binaural interaction effects that lead to reductions in energetic masking are obscured by reflections, a spatial separation advantage still can be obtained when the competing sound produces informational masking (e.g., Brungart, Simpson, & Freyman, 2005;Freyman, et al, 1999;Kidd, Mason, Brughera, & Hartmann, 2005;Rakerd, Aaronson, & Hartmann, 2006).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…In general, informational masking is most likely to occur when the target and masker are similar to one another (e.g., when both a speech target and a speech masker are recorded from talkers of the same sex). A number of studies have demonstrated that both energetic and, in particular, informational masking can be reduced by spatially separating the target from the masker (e.g., Brungart & Simpson, 2002;Freyman, Balakrishnan, & Helfer, 2004;Freyman, et al, 1999Freyman, et al, , 2001Freyman, Helfer, & Balakrishnan, 2005;Hawley, Litovsky, & Colburn, 1999) although the mechanisms leading to spatial separation advantage seem to differ between the two types of masking. Specifically, even when the head shadow and binaural interaction effects that lead to reductions in energetic masking are obscured by reflections, a spatial separation advantage still can be obtained when the competing sound produces informational masking (e.g., Brungart, Simpson, & Freyman, 2005;Freyman, et al, 1999;Kidd, Mason, Brughera, & Hartmann, 2005;Rakerd, Aaronson, & Hartmann, 2006).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Human sound source localization performance is very robust, even in the presence of multiple competing sounds and room reverberation [1]. The two main cues that are used by the auditory system to determine the azimuth of a sound source are interaural time differences (ITDs) and interaural level differences (ILDs) [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, human auditory system with just two ears has shown great performance for source separation [5,4] which has been studied under the name of computation auditory scene analysis (CASA) [2,16]. It is found that different monaural and binaural cues such as pitch, interaural level difference (ILD) and interaural phase difference (IPD) can be estimated and exploited to generate corresponding T-F masks to identify the T-F units of the mixtures' spectrograms dominated by each source.…”
Section: Introductionmentioning
confidence: 99%